STRATEGI BERSAING UNTUK MENINGKATKAN DAYA SAING SEKOLAH TINGGI TEOLOGIA DI UNGARAN - I Putu Ayub Darmawan; Sutriyono Sutriyono (Kelola: Jurnal Manajemen Pendidikan, 2016)
This study aimed to design a competitive strategy to improve the competitiveness of STT Simpson. This study was a research and development. The data were collected through observation, FGD (Focus Group Discussion) and interviews. Competitive strategies of STT Simpson are 1) Differentiation strategy: STT Simpson can offer theological education class in the evening to optimize the facilities owned for the churches in Ungaran and its surrounding; 2) Cost advantage strategy: STT Simpson has an advantage in some types of costs but STT Simpson still have to adjust the tuition course to prevent the gap with another STT and keep maintaining its competitiveness; 3) Focus strategy: STT Simpson perform its marketing by focusing on youth of the church around GKII; and 4) Marketing communication strategy with various forms of marketing communications utilizing the technologies esvolving by offering characteristics possessed.